(untitled) (Economics and region, 2017)
UDK 330.5:330.1:331.47 Oleksandr Kubatko, PhD in Economics, Associate professor. Sumy State University. Economic and environmental fluctuation of population health indicators. The paper deals with estimation of environmental and economic fluctuations impact on cyclical and trend components of health indicators. Using the Butterworth bandpass filter it was performed statistical decomposition of real environmental and economic data on the trend and cyclical components. The paper reveals the economic fluctuation with duration up to 8 years. Fluctuations of cardiovascular diseases are determined by such factors as fluctuations in air pollution (emissions of pollutants per square kilometer), fluctuations in the population age structure and by the fluctuations in new cases of alcoholism. The latter factor may reflect not only the dynamics of the incidence of alcoholism, but also the dynamics of socio-economic factors in the region. It was found that the amplitude logarithm of air pollution fluctuations ( in terms of emissions per square kilometer) is more than five times higher compared to the logarithm of heart disease fluctuations in the regions of Ukraine. The health fluctuations are appeared to be elastic with respect to fluctuations of population average age in the regions of Ukraine. Also it was found that air pollution fluctuations are inelastic with respect to fluctuations of health, the last situation can be explained by the environmental assimilation potential and adaptation capacity of humans. It was found that the increase of air pollution fluctuation by one percent lead to increase of cardio-vascular health fluctuation by 0,21 percent. Actually the presence of statistically significant links between of air pollution fluctuations and health fluctuations states that the changes in environmental quality are almost instantly reflected on the human morbidity. Keywords: economic and environmental fluctuations, economic development, air emissions, health of population.